The listening composer - Perle, George, 1915-2009 (The Ernest Bloch lectures, 1990)
George Perle takes us into the composer's workshop as he reevaluates what we call "twentieth-century music"--A term used to refer to new or modern or contemporary music that represents a radical break from the tonal tradition, or "common practice," of the preceding three centuries. He proposes that this music, in the course of breaking with the tonal tradition, presents coherent and definable elements of a new tradition. In spite of the disparity in their styles, idioms, and compositional methods, he argues, what unites Scriabin, Stravinsky, Bartok, and the Viennese circle (Schoenberg, Berg, and Webern) is more important than what separates them. If we are to understand the connections among these mainstream composers, we also have to understand their connections with the past